Comparative Analysis of Lower Genital Tract Microbiome Between PCOS and Healthy Women - Tu, Yaoyao; Zheng, Guangyong; Ding, Guolian; Wu, Yanting; Xi, Ji; Ge, Yingzhou; Gu, Hangchao; Wang, Yingyu; Sheng, Jianzhong; Liu, Xinmei; Jin, Li; Huang, Hefeng (Frontiers in Physiology, 2020)
PCOS women often have a history of infertility and poor pregnancy outcome, the character of the lower genital tract (LGT) microbiome of these patients is still unknown. We collected both vaginal and cervical canal swabs from 47 PCOS patients (diagnosed by the Rotterdam Criteria) and 50 healthy reproductive-aged controls in this study. Variable regions 3-4 (V3-4) were sequenced and analyzed. Operational taxonomic unit (OTU) abundance was noted for all samples. Taxa that discriminated between PCOS and healthy women was calculated by Linear discriminant analysis effect size (LEFSe). Results from 97-paired vaginal and cervical canal samples collected from 97 women [mean age 30(±4 years)] were available for analysis, using the Rotterdam Criteria, 47 women were diagnosed with PCOS (PCOS, n=47; Control, n=50). There was no significant difference between cervical canal microbiome and vaginal microbiome from the same individual, however Lactobacillus spp. was less abundant in both vaginal and cervical canal microbiome of PCOS patients. Several non-Lactobacillus taxa including Gardnerella_vaginalis_00703mash, Prevotella_9_other, Mycoplasma hominis, were more abundant in the LGT microbiota of PCOS patients. Conclusions: There is a difference between the microorganism in the LGT of patients with PCOS and healthy reproductive aged women.